2021
DOI: 10.1088/1402-4896/abfe87
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of electromagnetic waves in stationary anisotropic media

Abstract: In this paper we have investigated the fundamental properties of the solutions of Maxwell’s equations describing free electromagnetic waves in stationary anisotropic media, with tensor characteristics along the Z axis. A matrix of coefficients, the structure of the matrix of Maxwell’s equations, dispersion equations and indicatrix curves for a transparent anisotropic one-dimensional inhomogeneous conductive medium have been obtained. Exact analytical solutions in case of homogeneous anisotropic media are const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…where and µ represent the electric permittivity and magnetic permeability tensors [7,[12][13][14][15], respectively. The tensor γ measures the magnetic contribution to the electric displacement field D, while γ represents the electric contribution to the magnetic field H. Regarding the structure of constitutive relations (1a) and (1b), interesting scenarios of electromagnetic behavior may occur, e.g., in anisotropic media [4][5][6][7][12][13][14][15], Weyl semimetals [8,9,72], magnetized ferrites [10,11], and in chiral media and topological insulators [18][19][20]. Besides Eq.…”
Section: Electrodynamics In Simple Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…where and µ represent the electric permittivity and magnetic permeability tensors [7,[12][13][14][15], respectively. The tensor γ measures the magnetic contribution to the electric displacement field D, while γ represents the electric contribution to the magnetic field H. Regarding the structure of constitutive relations (1a) and (1b), interesting scenarios of electromagnetic behavior may occur, e.g., in anisotropic media [4][5][6][7][12][13][14][15], Weyl semimetals [8,9,72], magnetized ferrites [10,11], and in chiral media and topological insulators [18][19][20]. Besides Eq.…”
Section: Electrodynamics In Simple Mattermentioning
confidence: 99%
“…Such an effect is represented, for example, by Figs. (5) and (6), where the graphs indicate that Im[n(ω)] = 0 in the absorption range ω − < ω < ω + , with ω ± given in Eq. ( 75).…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The matrix of the coefficients   0 1 h B B Z dZ h   (16) has been introduced into this relationship, where   B Z is given by Eq. ( 14), the matrix p in the second approximation is defined by the formula…”
Section: During Propagation Of Long Electromagnetic Waves In Cholesteric Liquid Crystalsmentioning
confidence: 99%
“…It was shown that these SEV are effectively generated by the attenuated total reflection method. Processes in elastic anisotropic and anisotropic dielectric media and propagation of waves in anisotropic plates, electromagnetic waves in media with magnetoelectric effect [14][15][16][17], and waves in liquid crystals and thermoelastic media [18][19][20] were considered in [13] using the matricant method. Results of uniform description of wave processes in media with different physicomechanical properties were reported at the XVth All-Russian School-Seminar "Physics and Application of Microwaves" named after A. P. Sukhorukov (Waves-2016) [21].…”
Section: Introductionmentioning
confidence: 99%